Impact analysis of smartphone use and Youth Family Development (BKR) program on family disharmony in Magetan Regency - Puji Nurhayati; Pratama Dharmika Nugraha; Heidy Paramitha Devi; Andri Wahyu Utomo (Universitas Trunojoyo Madura, 2020)
This article examines the impact of the use of smart phone and BKR programs on family disharmony. Smartphone are devices that have both positif and negative effects. Indonesia is predicted to get a demographic bonus in 2020- 2030 with the highest number of teenagers, and the majority of smartphone users are teenagers. BKR is a program that serves to help parenting to avoid deviant behavior. This research uses quantitative methods, with primary data of 300 respondents. The sample of this study consisted of 150 PKK groups and 150 teenagers. Data collection technique is using questionnaire data. Data analysis technique is using path analysis and SPSS 21.0 software. The results of the study stated that the use of smartphone had a negative and not significant effect on family disharmony, smartphone usage had a negative and significant effect on BKR program and smartphone usage had a negative and significant effect on family disharmony. The use of a smart phone does not have an impact on family disharmony because of effective communication between family members. The existence of the BKR program is still needed to assist families in fostering their teenagers so that it is wiser to use a smartphone.